Effects of the Proprioceptive Neuromuscular Facilitation Contraction Sequence on Motor Skill Learning-Related Increases in the Maximal Rate of Wrist Flexion Torque Development - Green, Lara A.; McGuire, Jessica; Gabriel, David A. (Frontiers in Human Neuroscience, 2021)
Background: The proprioceptive neuromuscular facilitation (PNF) reciprocal contraction pattern has the potential to increase the maximum rate of torque development. However, it is a more complex resistive exercise task and may interfere with improvements in the maximum rate of torque development due to motor skill learning, as observed for unidirectional contractions. The purpose of this study was to examine the cost-benefit of using the PNF exercise technique to increase the maximum rate of torque development. Methods: Twenty-six participants completed isometric maximal extension-to-flexion (experimental PNF group) or flexion-only (control group) contractions at the wrist. Ten of the assigned contractions were performed on each of three sessions separated by 48-h for skill acquisition. Retention was assessed with 5 contractions performed 2-weeks after acquisition. Torque and surface electromyographic (sEMG) activity were analyzed for evidence of facilitated contractions between groups, as well as alterations in muscle coordination assessed across test sessions. The criterion measures were: mean maximal isometric wrist flexion toque; the maximal rate of torque development (dτ/dtmax); root-mean-square error (RMSE) variability of the rate of torque versus torque phase-plane; the rate of wrist flexion muscle activation (Q30); a coactivation ratio for wrist flexor and extensor sEMG activity; and wrist flexor electromechanical delay (EMD). Results: There were no significant differences between groups with respect to maximal wrist flexion torque, dτ/dtmax or RMSE variability of torque trajectories. Both groups exhibited a progressive increase in maximal strength (+23.35% p < 0.01, η2 = 0.655) and in dτ/dtmax (+19.84% p = 0.08, η2 = 0.150) from the start of acquisition to retention. RMSE was lowest after a 2-week rest interval (−18.2% p = 0.04, η2 = 0.198). There were no significant differences between groups in the rate of muscle activation or the coactivation ratio. There was a reduction in coactivation that was retained after a 2-week rest interval (−32.60%, p = 0.02, η2 = 0.266). Alternatively, EMD was significantly greater in the experimental group (Δ 77.43%, p < 0.01, η2 = 0.809) across all sessions. However, both groups had a similar pattern of improvement to the third consecutive day of testing (−16.82%, p = 0.049, η2 = 0.189), but returned close to baseline value after the 2-week rest interval. Discussion: The wrist extension-to-flexion contraction pattern did not result in a greater maximal rate of torque development than simple contractions of the wrist flexors. There was no difference between groups with respect to motor skill learning. The main adaptation in neuromotor control was a decrease in coactivation, not the maximal rate of muscle activation.